KAJIAN MOLEKULER PADA PROBIOTIK ASAL AIR SUSU IBU DALAM SINTESIS EKSOPOLISAKARIDA (EPS) - Hamiyawati Qoimatu Dini Alfaruqi; Nosa Septiana Anindita; Arif Bimantara (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2021)
Molecular Studies on Probiotic of Human Breast Milk in the Synthesis of Exopolysaccharide (EPS)  The glucosyltransferase (gtf) gene has an important role in exopolysaccharide (EPS) synthesis in probiotic bacteria. The EPS produced is associated with the adhesion ability of bacteria to the intestinal mucosa. Therefore, the gtf gene can be used as a parameter in the selection of potential probiotic through a molecular approach. This study was conducted to determine the presence of the gtf gene in probiotic from human breast milk using PCR technique. The methods in this study include the following: reculture of probiotic isolates, DNA isolation, amplification of the 16S rRNA gene using universal primers (pA and pB), amplification of specific LAB primers (LABfw and LABrv), specific primary design for the gtf gene, and the amplification of the gtf gene. The results of 16S rRNA gene amplification using universal primers obtained the amplicons of 500-1,000 bp in size. The results of amplification using specific LAB primers obtained an amplicon of about 700 bp in all isolates. The results of amplification of the gtf gene using a specific primer produced an amplicon of 325 bp in all isolates. Based on this study, it was concluded that 16 probiotic isolates from human breast milk were proven to have the gtf gene. Gen glukosiltransferase (gtf) memiliki peran penting dalam sintesis eksopolisakarida (EPS) pada bakteri probiotik. EPS yang diproduksi berhubungan dengan kemampuan adhesi bakteri pada mukosa usus. Oleh karena itu, gen gtf dapat dijadikan sebagai salah satu parameter dalam seleksi probiotik potensial melalui pendekatan molekuler. Penelitian ini dilakukan untuk mengetahui adanya gen gtf pada probiotik asal air susu ibu (ASI) menggunakan teknik PCR. Metode pada penelitian ini meliputi: reculture isolat probiotik, isolasi DNA, amplifikasi gen 16S rRNA menggunakan primer universal (pA dan pB), amplifikasi primer spesifik BAL (LABfw dan LABrv), desain primer spesifik untuk gen gtf dan amplifikasi gen gtf. Hasil amplifikasi gen 16S rRNA menggunakan primer universal diperoleh amplikon berukuran antara 500-1.000 bp. Adapun hasil amplifikasi menggunakan primer spesifik BAL diperoleh amplikon berukuran sekitar 700 bp pada seluruh isolat. Hasil amplifikasi gen gtf menggunakan primer spesifik menghasilkan amplikon berukuran sekitar 325 bp pada seluruh isolat. Berdasarkan penelitian ini dapat disimpulkan bahwa 16 isolat probiotik asal ASI terbukti memiliki gen gtf.